An immense world: how animal senses reveal the hidden realms around us (Random House Publishing Group, Random House, 2022)
"The Earth teems with sights and textures, sounds and vibrations, smells and tastes, electric and magnetic fields. But every animal is enclosed within its own unique sensory bubble, perceiving but a tiny sliver of an immense world. This book welcomes us into a previously unfathomable dimension--the world as it is truly perceived by other animals. We encounter beetles that are drawn to fires (and fireworks), songbirds that can see the Earth's magnetic fields, and brainless jellyfish that nonetheless have complex eyes. We discover that a crocodile's scaly face is as sensitive as a lover's fingertips, that the eyes of a giant squid evolved to see sparkling whales, and that even fingernail-sized spiders can make out the craters of the moon. We meet people with unusual senses, from women who can make out extra colors to blind individuals who can navigate using reflected echoes like bats. Yong tells the stories of pivotal discoveries in the field, and also looks ahead at the many mysteries which lie unsolved"--
The only true voyage , Leaking sacks of chemicals : smells and tastes , Endless ways of seeing : light , Rurple, grurple, yurple : color , The unwanted sense : pain , So cool : heat , A rough sense : contact and flow , The rippling ground : surface vibrations , All ears : sound , A silent world shouts back : echoes , Living batteries : electric fields , They know the way : magnetic fields , Every window at once : uniting the senses , Save the quiet, preserve the dark : threatened sensescapes.

Animals make us human: creating the best life for animals (Houghton Mifflin Harcourt, HarperCollins, 2009)
Drawing on the latest research and her own work, Grandin identifies the core emotional needs of animals and explains how to fulfill them for dogs and cats, horses, farm animals, and zoo animals.
1. What do animals need? , 2. A dog's life , 3. Cats , 4. Horses , 5. Cows , 6. Pigs , 7. Chickens and other poultry , 8. Wildlife , 9. Zoos.

Snack, snooze, skedaddle: how animals get ready for winter (Millbrook Press, Lerner Publishing Group, 2019)
There is more than one way for animals to prepare for winter. Some, such as mice, foxes, and moose, simply tolerate the cold. Of course black bears hibernate, but chipmunks, wood frogs, and garter snakes do too. And then there are the creatures that migrate, including hummingbirds, blue whales, and even earthworms!

Animals with cameras ([Publisher not identified], 2018)
Wildlife cameraman Gordon Buchanan and animal behaviorists join forces to explore stories of animal lives 'told' by the animals themselves. The series explores the secret side of the animal kingdom where human cameramen can't go, and camera-wearing animals film their own stories. Sprint across the savannah with a cheetah, plunge into the ocean with a seal, and swing through the trees with a chimp!

Tamed & untamed: close encounters of the animal kind (Chelsea Green Publishing, 2017)
"Tamed and Untamed -- a collection of essays penned by two of the world's most celebrated animal writers, Sy Montgomery and Elizabeth Marshall Thomas -- explores the minds, lives, and mysteries of animals as diverse as snails, house cats, hawks, sharks, dogs, lions, and even octopuses. Drawing on stories of animals both wild and domestic, the two authors, also best friends, created this book to put humans back into the animal world. The more we learn about what other animals think and do, they explain, the more we understand ourselves as animals, too. Writes Montgomery, "The list of attributes once thought to be unique to our species -- from using tools to waging war -- is not only rapidly shrinking, but starting to sound less and less impressive when wecompare them with other animals' powers." With humor, empathy, and introspection, Montgomery and Thomas look into the lives of all kinds of creatures -- from man's best friend to the great white shark -- and examine the ways we connect with our fellow species. Both authors have devoted their lives to sharing the animal kingdom's magic with others, and their combined wisdom is an indispensable contribution to the field of animal literature. The book contains a foreword by Vicki Constantine Croke, author ofthe bestseller"--

Lots of things to know about animals (EDC Publishing, 2022)
A collection of amazing facts exploring the wonders of the animal world. You'll never guess how monkeys clean their teeth, why penguins steal stones, which baby animal is bigger than its parents or just how high bumblebees can fly! All is revealed in this delightful information book, filled with friendly, humorous pictures and quirky, surprising facts about all kinds of animals. You'll want to share this book with everyone you know!

Does it fart?: the definitive field guide to animal flatulence (Hachette Books, 2018)
"Dogs do it. Millipedes do it. Dinosaurs did it. You do it. I do it. Octopuses don't (and nor do octopi). Spiders might do it: more research is needed. Birds don't do it, but they could if they wanted to. Herrings do it to communicate with each other. In 2017 zoologist Dani Rabaiotti's teenage brother asked her a most teenaged question: Do snakes fart? Stumped, Rabaiotti turned to Twitter. The internet did not disappoint. Her innocent question spawned the hashtag #doesitfart and it spread like a noxious gas. Dozens of noted experts began weighing in on which animals do and don't fart, and if they do, how much, how often, what it's made of, what it smells like, and why. Clearly, the public demands more information on animal farts. Does it Fart? fills that void: a fully authoritative, fully illustrated guide to animal flatulence, covering the habits of 80 animals in more detail than you ever knew you needed. What do hyena farts smell especially bad? What is a fossa, and does it fart? Why do clams vomit but not fart? And what is a fart, really? Pairing hilarious illustrations with surprisingly detailed scientific explanations, Does it Fart? will allow you to shift the blame onto all kinds of unlikely animals for years to come"--
Herring , Goat , Sonoran coral snake , Baboon , Millipede , Beaded lacewing , Horse , Kangaroo , Bolson pupfish , African wild dog , Bat , Portuguese man o' war , Parrot , Unicorn , Sea anemone , Spider , Rhinoceros , Elephant , Bearded dragon , Cheetah , Zebra , Dinosaur , Lion , Goldfish , Termite , Whale , African buffalo , Brown rat , Honey badger , Giraffe , Striped skunk , Red fox , Ferret , Seal and sea lion , Guinea pig , Grizzly bear , Sea cucumber , Bird , Llama , Sloth , Salamander , Chimpanzee , Silver-spotted skipper , Eastern hognose snake , Sand tiger shark , Frog , American cockroach , Orangutan , Rabbit , Dog , Painted turtle , Colobus monkey , West Indian manatee , Spotted hyena , Bobcat , Python , Cat , Tortoise , Camel , Iguana , Gecko , Octopus , Mongoose , Gorilla , Woodlouse , Fossa , Soft-shelled clam , Snow leopard , Cow , Dolphin , Lemur , Diving beetle , Hippopotamus , Koala , Tapir , Megalodon , Wombat , Warthog , Hamster , Human.

Inside of a dog: what dogs see, smell, and know (Scribner, Simon & Schuster Books for Young Readers, 2016)
Do you want to know what dogs are thinking? What they're feeling? Now you finally can. The answers will surprise and delight young readers as scientist and dog-owner Alexandra Horowitz explains how dogs perceive their daily worlds, each other, and that other quirky animal, the human. --Publisher

Count down to fall (Sylvan Dell Pub, 2009)
Rhymed text and illustrations invite readers to count backwards from ten to one and to learn about the bright, colorful leaves and the trees from which they fall.

Animal odd couples (PBS Distribution, 2013)
Enter stories of the most unlikely cross-species relationships imaginable: a chimp bottle-feeding tiger cub, a giant tortoise snuggling with a baby hippo, a black crow parenting a meerkat. Look at these remarkable relationships first hand, and through caregivers, biologists, and animal behaviorists. Explore what they suggest about the nature of animal emotions.

The big, bad book of beasts: the world's most curious creatures (William Morrow, an imprint of HarperCollinsPublishers, 2013)
"A one-of-a-kind treasury of the most strange and fascinating knowledge and lore about animals. Largo tells us their most fascinating secrets and reveals fact after astonishing--and often hilarious--fact about their oddest behavior. Largo also looks at the beasts we created with our imaginations, as well as ones long gone"--
Introduction , The big, bad book of beasts, A to Z.

Furry logic: the physics of animal life (BloomsburyS Sigma, 2017)
'Furry Logic' looks in detail at the animals that use cool physics in weird and intriguing ways as part of their daily battle to survive. It details the role of physics in the lives of a number of animals, as uncovered by scientists researching in the field.

Whoa, that's strange! (Ugh! yuck! and whoa!, ,, 2018)
"Describes bizarre habits of the spotted hyena, basilisk lizard, snow monkey, and other animals. Includes large photographs and relevant information about each animal presented"--

What a jerk! (Ugh! yuck! and whoa!, ,, 2018)
"Describes the strange and rude behaviors of chimpanzees, raccoons, seagulls, and other animals. Includes large photographs and relevant information about each animal presented"--

Unlikely friendships: 47 remarkable stories from the animal kingdom (Workman Publishing, 2011)
Presents a collection of stories about animals who have forged unlikely, abiding bonds with other animals of different species, from Koko the gorilla and All Ball the kitten to Owen the hippo and the tortoise Mzee.

Glowing animals (National Geographic kids readers. Level 1, ,, 2019)
Introduces bioluminescence in animals, describing how and why certain animals emit light.

Surviving animal attacks (Shockzone. True survival stories, ,, 2014)
Wild animals are often cute. But even the most adorable creatures can sometimes snap and bite your face off. Sharks and grizzly bears certainly have the power to rip people limb-from-limb. But animals such as chimpanzees or even pet dogs can also cause a lot of bodily harm. See how these people survived some much-too-close encounters. --Publishers description from Amazon.com
Attacked! , A grisly grizzly attack , The scorpion queen , Pet dog attack , Torn apart by a chimpanzee , Big Joe strikes , Attacked by a shark, saved by dolphins , 10 dealiest animals in the world.

My encyclopedia of very important animals (New York, NY, DK Publishing, 2017)
From peacocks and frogs to sharks and dogs, My Encyclopedia of Very Important Animals is perfect for the curious little animal lover in your life. Mixing photography and charming illustration, kids will find out important things about the wonderful world of animals from what they eat, what they do, and why people are animals, too. My Encyclopedia of Very Important Animals is a friendly book that gets children learning, reading, and laughing!

Get the scoop on animal puke!: from zombie ants to vampire bats, 251 cool facts about vomit, regurgitation, & more! (Imagine! Publishing, 2014)
Discusses animal vomit and the many purposes it serves, including scaring and distracting predators, feeds family and neighbors, protects animals from poisoning, and aids with digestion.

Zoobots: wild robots inspired by real animals (Kids Can Press, 2014)
Learn about robots inspired by animals.
Wild about robots , Snooorrrff! (Shrewbot) , Slither! (Uncle Sam) , Stalk! (Whitesides' color changer) , Squeeze! (Octobot) , Spray! (Ole pill bug) , Stick! (Stickybot III) , Ripple! (Ghostbot) , Whip! (Nanobot) , Swoop! (Robobat) , Creep! (Dynamic Autonomous Sprawled Hexapod) , Swarm! (AirJelly and AquaJelly) , Impersonate! (Geminoid F) , Zoobot future?